2016
DOI: 10.1615/forumimmundisther.2016017095
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Natural Killer Cells by Probiotics

Abstract: During the last decade, probiotics have been established to be important mediators of host immunity. Their effects on both innate and adaptive immunity have been documented in the literature. Although several reports have correlated different strains of bacteria as probiotics, their effects on immunity vary. Clearly, there is a complex interplay between various constituents of probiotics and the immune response in humans. The role of probiotics on natural killer (NK) cells in the gut has been the subject of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 83 publications
(113 reference statements)
0
38
1
2
Order By: Relevance
“…Probiotics exert beneficial effects on the intestinal mucosa via various mechanisms, including the inhibition of the growth and binding of pathogenic bacteria, amelioration of the epithelial barrier function, and modulation of the local and systemic immunity of hosts [ 11 ]. Through these alterations, specific probiotic strains have been demonstrated to enhance innate immunity, phagocytosis, and NK cell activity primarily; however, acquired immunity remains unaffected [ 22 ]. Among the available strains, Lactobacillus strains have been the most investigated, which have exhibited beneficial effects on gut health [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotics exert beneficial effects on the intestinal mucosa via various mechanisms, including the inhibition of the growth and binding of pathogenic bacteria, amelioration of the epithelial barrier function, and modulation of the local and systemic immunity of hosts [ 11 ]. Through these alterations, specific probiotic strains have been demonstrated to enhance innate immunity, phagocytosis, and NK cell activity primarily; however, acquired immunity remains unaffected [ 22 ]. Among the available strains, Lactobacillus strains have been the most investigated, which have exhibited beneficial effects on gut health [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we used a blend of five Lactobacillus strains, namely L. acidophilus, L. helveticus, L. rhamnosus, L. fermentum , and L. bulgaricus . Reportedly, L. acidophilus and Bifidobacterium breve increase the activity of NK cells and enhance their activation [ 24 ]; however, a more extensive variety of Lactobacillus strains has been known to increase the number and activity of NK cells because of an interaction between NK and dendritic cells [ 22 ]. Furthermore, some studies have reported that the activity of NK increased overall and was not specific to any individual strain of commercial lactobacilli or bifidobacteria [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, changes in microbiome have been reported to modulate IAV infection (Ichinohe et al, 2011;Yaqoob, 2014;Chen et al, 2017a;Yitbarek et al, 2018). As gut microbiota are also suggested to play an important role in the development and function of lymphoid cells, including NK cells (Kamada and Núñez, 2013;Aziz and Bonavida, 2016), nF1-fortified yogurt may induce immunological responses enhancing the NK cell activity and exhibit both protective and prophylactic effects against IAV infection by changing gut microbiome composition. Further studies should investigate the relationship between alterations in gut microbiota and immunological activities following the daily uptake of nF1-fortified yogurt.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, specific commensal bacterial strains have been linked to modulation of NK cells. Several reports established that bacteria within the Lactobacillus genus can induce IFNγ and cytotoxicity responses in intestinal NK cells as a result of IL-12 production by dendritic cells after TLR engagement with bacteria (Fink et al, 2007, Koizumi et al, 2008, Aziz and Bonavida, 2016. Furthermore, Bacteroides fragilis can stimulate innate and adaptive immune pathways directly through TLR signaling and indirectly by inducing cytokine production (Troy and Kasper, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rodents and humans have shown that specific probiotic microorganisms enhance intestinal NK cell activity and cytokine production (Aziz and Bonavida, 2016) either directly via their interaction with receptors expressed on NK cells (Carrillo-Bustamante et al, 2016, Temperley et al, 2008, or indirectly via cytokine production of resident myeloid or epithelial cells (Sonnenberg and Artis, 2012). Also the adaptive immune system can be modulated via interactions with the microbiota (Brisbin et al, 2012, Gao et al, 2017, Siwek et al, 2018, Yitbarek et al, 2019, or indirectly through innate immune cell activities.…”
Section: Introductionmentioning
confidence: 99%